2020
DOI: 10.3390/membranes10100294
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Interaction of a Novel Semi-Synthetic Peptide with Model Lipid Membranes

Abstract: Most linear peptides directly interact with membranes, but the mechanisms of interaction are far from being completely understood. Here, we present an investigation of the membrane interactions of a designed peptide containing a non-natural, synthetic amino acid. We selected a nonapeptide that is reported to interact with phospholipid membranes, ALYLAIRKR, abbreviated as ALY. We designed a modified peptide (azoALY) by substituting the tyrosine residue of ALY with an antimicrobial azobenzene-bearing amino acid.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…S7 † ), we further elucidated the atomic-level details of a lead PrAMP, octofluorobiphenyl dimer-NHNH 2 7, adsorbed on and permeating through a mixed phospholipid membrane bilayer via molecular dynamics simulations. Although phosphatidylethanolamine (PE), rather than neutral phosphatidylcholine (PC), is more commonly found in bacterial membranes, palmitoyloleoylphosphatidylcholine (POPC) and palmitoyloleoylphosphatidylglycerol (POPG) mixtures are frequently used as proxies for bacterial membranes in experimental studies and molecular dynamics (MD) simulations of protein- 44 and peptide 45 -lipid interactions, as the use of PC confers the advantage of producing a membrane with less curvature stress 46 compared to PE. For each bilayer adsorption simulation, a pre-equilibrated mixed bilayer composed of POPC and POPG in a 7 : 3 ratio serves as a model of Gram negative inner membranes.…”
Section: Resultsmentioning
confidence: 99%
“…S7 † ), we further elucidated the atomic-level details of a lead PrAMP, octofluorobiphenyl dimer-NHNH 2 7, adsorbed on and permeating through a mixed phospholipid membrane bilayer via molecular dynamics simulations. Although phosphatidylethanolamine (PE), rather than neutral phosphatidylcholine (PC), is more commonly found in bacterial membranes, palmitoyloleoylphosphatidylcholine (POPC) and palmitoyloleoylphosphatidylglycerol (POPG) mixtures are frequently used as proxies for bacterial membranes in experimental studies and molecular dynamics (MD) simulations of protein- 44 and peptide 45 -lipid interactions, as the use of PC confers the advantage of producing a membrane with less curvature stress 46 compared to PE. For each bilayer adsorption simulation, a pre-equilibrated mixed bilayer composed of POPC and POPG in a 7 : 3 ratio serves as a model of Gram negative inner membranes.…”
Section: Resultsmentioning
confidence: 99%
“…In a simulation study carried out by Koivuniemi et al, MD simulations of these derivatives interacting with both prokaryotic and eukaryotic model membranes found evidence of important differences in their behavior in the two membrane types [843]. Additionally, antimicrobial peptides can have their desired properties enhanced through the introduction of non-natural amino acids, e.g., the azoALY peptide derived from ALY (full sequence: ALYLAIRKR) by functionalization of the sole tyrosine residue present with an azobenzene group [844]. Both MD simulations and experimental studies have found evidence that this modification results in a peptide with an enhanced interaction with lipid bilayers.…”
Section: A Clear Case Of Drug Membrane Interaction As Mechanism Of Action-antimicrobial Agentsmentioning
confidence: 99%
“…Lipids modified with azobenzene have received particular attention in recent years because photolipids, lipophilic molecules, can be rapidly converted from a linear to a folded form by exploiting the isomerization of the -N=N- double bond. Some authors have also used azobenzene molecules to synthesize semi-synthetic peptides, by evaluating their ability to penetrate through membranes and their behavior through the phospholipid bilayer of GUVs (Giant unilamellar vesicles) and LUVs (large unilamellar vesicles) [ 75 ]. Similarly, azobenzene molecules can be included in polymer matrices, or even be used as pendants covalently linked to polymer chains to obtain materials with various properties, such as antimicrobial.…”
Section: Azo Compounds In Antimicrobial Peptides and Polymersmentioning
confidence: 99%